2010
DOI: 10.1210/en.2010-0089
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency in Mice Impairs Colonic Antibacterial Activity and Predisposes to Colitis

Abstract: Vitamin D insufficiency is a global health issue. Although classically associated with rickets, low vitamin D levels have also been linked to aberrant immune function and associated health problems such as inflammatory bowel disease (IBD). To test the hypothesis that impaired vitamin D status predisposes to IBD, 8-wk-old C57BL/6 mice were raised from weaning on vitamin D-deficient or vitamin D-sufficient diets and then treated with dextran sodium sulphate (DSS) to induce colitis. Vitamin D-deficient mice showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
122
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(132 citation statements)
references
References 49 publications
9
122
0
1
Order By: Relevance
“…In the colon, Cramp expression was not different in the Cyp KO mice compared with WT mice. Decreased expression of angiogenin-4 mRNA and protein has been reported in vitamin D-deficient mice (45). There were no differences in several of the antibacterial peptides, mucins, etc.…”
Section: Discussionmentioning
confidence: 59%
“…In the colon, Cramp expression was not different in the Cyp KO mice compared with WT mice. Decreased expression of angiogenin-4 mRNA and protein has been reported in vitamin D-deficient mice (45). There were no differences in several of the antibacterial peptides, mucins, etc.…”
Section: Discussionmentioning
confidence: 59%
“…Once bacteria are engulfed, they are incorporated into phagolysosomes and exposed to reactive oxygen species and other bacteriotoxic compounds, which eventually results in bacterial lysis. The stimulation of microglia with TLR agonists is dose dependent (reference 28 and this study), and the efficacy of the phagocytic activity of reactive microglia depends not only on their ability to ingest bacteria but also on the pathogen's ability to modulate phagocyte signaling (49,50). This may be an additional reason why we found small differences in the phagocytosis rate between vitamin D-deficient and -sufficient microglia which failed to reach statistical significance at many individual concentrations tested.…”
Section: Discussionmentioning
confidence: 66%
“…Our experiments were performed with mouse microglial cells. Although the innate antibacterial activity of vitamin D has been thought to be restricted to primates that express the promoter vitamin D response element (VDRE) required for vitamin D-mediated transcriptional regulation of antibacterial proteins (44), some mouse antimicrobial molecules such as angiogenin-4 (Ang4) also appear to be influenced by vitamin D (49). Although the function of Ang4 appears to be restricted to specific areas of the gastrointestinal tract, this observation underlines the versatility of vitamin D as a promoter of antibacterial activity in different tissues and animal species (34).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that 1,25(OH) 2 D 3 and VDR play a role in the innate immunity against bacterial infections in the colon. It has been observed that bacterial infiltration of the colon is higher in vitamin D-deficient animals than in controls (Lagishetty et al 2010). Accordingly, in CRC cells 1,25(OH) 2 D 3 induces the expression of cathelicidin anti-microbial peptide in a VDRE-dependent mechanism (Gombart et al 2005) and VDR mediates the up-regulation of the anti-microbial peptide b-defensin-2 by dietary sulphoraphane (Schwab et al 2008).…”
Section: Angiogenesismentioning
confidence: 99%